Do critical audit matters signal higher quality of audited financial information? Evidence from asset impairment. Issue 2 (3rd April 2019) - Wu, Xi; Fan, Yujiang; Yang, Yulong
ABSTRACT: Chinese auditing standards mandate the disclosure of critical audit matters (CAMs) in audit reports for all listed companies since 2017. Risk-oriented auditing requires auditors to assess material misstatement risks and provide reasonable assurance on financial statements that should reflect the firm's underlying economics, regardless whether a CAM is disclosed. However, given a material misstatement risk, if some auditors effectively identify it as a CAM while others do not, the financial information with a CAM would exhibit higher quality than that without a CAM, leading to a positive association between CAM disclosure and the audited information quality. Using asset impairment-related CAMs, we show the relation between asset impairment and worsened economics is notably stronger for companies with an impairment-related CAM than those without any. Further, this association is more pronounced in smaller audit firms. Our findings reveal inadequate implementation of risk-oriented auditing, particularly in audit firms with greater resource constraints.